TINDAK TUTUR ILOKUSI PADA NOVEL GENDUK KARYA SUNDARI MARDJUKI - Sari, Laila; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe researcher chooses assertive ilocutionary speech acts and directives as the focus of research because they are speeches that often occur in everyday life. Researchers are interested in choosing the Genduk novel by Sundari Mardjuki because the novel can be used as an example of real human life. Researchers and readers can also take lessons from read novels.The problem discussed in this study is how the context and function of assertive and direct illocutionary speech acts in the Genduk novel by Sundari Mardjuki. The aim of this research was to describe the context and function of assertive and direct illocutionary speech acts in the Genduk novel by Sundari Mardjuki. The benefits of this research are expected to be a means for readers to open their horizons in learning the right speech in their daily activities.The method used in this research was descriptive method. The form of this study used a qualitative form, this form displays the analysis of the data obtained. The data source in this study was Genduk's novel by Sundari Mardjuki. The data in this study were assertive and directive illocutionary speech acts. Data collection techniques with documentation techniques, reading techniques, and note taking techniques.The results of data analysis on all conversations between speakers and speech partners in Sundari Mardjuki's Genduk novel were obtained and summarized as follows. 1) Assertive ilocutionary speeches consist of 41 utterances consisting of utterances stating 7 utterances, telling 26 utterances, uttering 2 utterances, demanding and reporting 4 utterances. 2) The directive ilokusi speech acts consist of 32 utterances consisting of speech ordered 8 utterances, asking for 1 speech, asking for 10 utterances, suggesting 1 speech, advising 12 utterances.Â Keywords: form and purpose, ilocution, Novel Genduk